Thin-shell wormholes in (2 + 1) -dimensional F(R) theories - Bejarano, Cecilia Soledad (2021)
We construct a broad family of thin-shell wormholes with circular symmetry in (2 + 1) -dimensional F(R) theories of gravity, with constant scalar curvature R. We study the stability of the static configurations under perturbations preserving the symmetry. We present examples of charged thin-shell wormholes which are asymptotically anti-de Sitter at both sides of the throat. We show that stable solutions are possible when suitable values of the parameters are taken.